5. A new paradigm forest development in Sambelia, East Lombok: A Clean Development Mechanism (CDM) approach - Abdullah Usman (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2006)
Abstrak Tulisan ini menyajikan pendekatan baru dalam pembangunan kehutanan yang diujicoba di Sambelia Lombok Timur: Pendekatan CDM dengan penekanan pada kajian keberadaan proyek. Penentuan lokasi dilakukan secara sengaja (pusposive) yaitu desa Labuan Pandan, mewawancarai petani, pemerintah, LSM dan universitas masing masing 25, 2, 2 dan 3 responden. Dengan menggunakan quessioner yang disediakan CDM proyek, wawancara mendalam dilakukan dengan semi struktur langsung. Data sekunder dikumpulkan dari institusi yag relevan. Studi ini mengungkapkan bahwa pendekatan CDM menjajikan banyak keunggulan: ekologi, ekonomi dan finansial. Kehadiran CDM kurang dikenal masyarakat dan karenanya perlu sosialisasi yang lebih intensif agar masyarakat dapat memberikan dukungan optimal. Peranan lembaga donor sangat menentukan keberhasilan pendekatan ini. Abstract This paper presents the implementation of a new paradigm forest development in Sambelia, East Lombok: a CDM approach. The target village was selected on purpose, namely: Labuan Pandan Village. Respondents consist of 25 farmers, 2 local government representatives, 2 NGO representatives, 3 university representatives. Primary data were collected using quessionaire provided by CDM Project. In-depth interview was applied using semi structure direct question. Secondary data were collected from relevant institution such as East Lombok District Office, Sambelia Sub District Office, and from Statistic Office. This study recorded that the CDM approach promises many benefits: ecology, economy and financial. The presence of CDM is less well known by local people and therefore it needs to be socialized more intensively to enhance the support and stake holders participation. The role of funding countries plays the key determinant factor for the approach.